Studi Analisis Perilaku Mencuci Tangan Terhadap Kepadatan Koloni Bakteri Sebelum dan Setelah Mencuci Tangan Pada Mahasiswa - Diah Wulandari Rousdy, Dessy Kartika, Rahmawati (Jurnal Protobiont, 2017)
Handwashing with soap is a healthy behavior that has scientifically been proved to prevent the spread of infectious diseases. Students who are active on campus have risk factors of being contaminated by bacteria. This research aims to determine the correlation between the number of bacterial colonies on the palms and handwashing practices among students, and the difference between the number of bacterial colonies before and after washing hands with soap. This research used a pour plate method in accordance with the Standard Plate Count Method. The samples were 35 students. Based on the t-test, handwashing with soap showed a decrease in the number of bacterial colonies than before washing hands with soap, namely 1751.3 CFU / cm2 becoming 905.5 CFU / cm2 after washing hands. The logistic regression analysis and descriptive test showed that there is a correlation between the number of bacterial colonies on the palms and hand washing practices among students.